Propagation of Tinospora cordifolia (Willd.) Miers Ex Hook. F. & Thoms. Through Mature Vine Cuttings and their Field Performance - Mishra, Yogeshwar; Usmani, Gufran; Chawhaan, Pravin H.; Mandal, A. K. (Indian Forester, 2010)
The study explores the scope of clonal propagation of Tinospora cordifolia Willd. Miers ex Hook. F. & Thorns. (Guduchi) by vine cutting. Mature cuttings were collected and treated with different concentrations of hormones viz. 100 ppm, 200 ppm and 300 ppm of IBA (Indole-3-Butyric Acid), NAA (Napthalene-6-Acetic Acid) and IAA (Indole-3-Acetic Acid). Sprouting and rooting capacity of the cuttings were assessed in open environment. Sampling was done after three months of planting. Data reveled that IBA significantly increased sprouting, rooting and root length as compared to control and other auxins. Among different concentrations applied lOOppm IBA significantly enhanced the rooting ability of T. cordifolia cuttings. Further, IBA (lOOppm) treated cutlings were found to be best for maximum plant length (364.73 cm) and number of branches (3.42) after six months of transfer of the plants in the field.